The Association of T45G Polymorphism in the Adiponectin Gene with Some Hormonal Parameters in Iraqi Women with Polycystic Ovary Syndrome (Medico Legal Update, 2020)
This study was reflected on the correlations between the polycystic ovary syndrome (PCOS) and a SingleNucleotide Polymorphism (SNP) T45G in the adiponectin gene among Iraqi infertile women with polycysticovary syndrome. Eighty primary infertile women with PCOS, sixty-two secondary infertile women withPCOS and 50 healthy fertile women in Iraq were included in this study, Blood samples were collectedfrom the infertility clinic in Azadi Teaching Hospital and AL-Salam Hospital. The age of infertile andfertile women was ranged from 18 to 46 years. Results showed association between T45G polymorphismin the adiponectin gene and infertile PCOS women. Moreover, infertile women with PCOS with thesepolymorphisms have been reported to have higher LH, FSH and prolactin concentrations and BMI. Inconclusion 45T?G polymorphisms have been shown to be associated with an increased risk of PCOSwomen with PCOS with these polymorphisms have been reported to have higher LH, FSH and prolactinconcentrations and BMI